Reforming Budget System Laws - Fainboim Yaker, Israel (Technical Notes and Manuals; Technical Notes and Manuals ;, 2010)
This paper discusses the need for reforming budget system laws (BSLs). The outcomes of the budget process depend heavily on whether there are clear rules for formulating, executing, and reporting on the annual budget, as well as a clear statement of medium-term fiscal policy objectives. These rules are usually specified in a BSL. This paper analyzes the relationship between the BSL, the constitution, and the wider legal framework. It also discusses how a BSL should be adapted to a country's political arrangements.